Hubungan Riwayat Prematuritas dengan Keterlambatan Bicara pada Balita di Ruang Tumbuh Kembang Anak RSUD Ulin Banjarmasin: Correlation Between History of Prematurity with Speech Delay in Toddler in the Children’s Growth Room, Ulin Hospital Banjarmasin - Noorlinda, Noorlinda; Malisa Ariani; Paul Joae Brett Nito (Journal of Health (JoH), 2025)
The ability to speak is one of the abilities that is very important and must be possessed by children, because the ability to speak is considered a fundamental ability. It is very important to pay attention to children's speaking abilities, so that speech delays do not occur in children (speech delay). Prematurity is one of the causes of speech delays in children. To determine the relationship between a history of prematurity and speech delay in children aged 2-5 years. This type of quantitative research is analytic observational with a retrospective approach. The research sample was 46 respondents using purposive sampling technique. The data collection tool used observation sheets for the history of prematurity and recapitulation of pediatric patient visit data based on a doctor's diagnosis. Univariate and bivariate data analysis using chi square. A total of 19 people (41.3%) respondents had a history of prematurity and speech delays in 19 people (41.3%). There is a relationship between a history of prematurity and speech delay in children aged 2-5 years (p=0.000 <0.005). There is a relationship between a history of prematurity and speech delay in children aged 2-5 years. The thing that must be considered so that children experience appropriate language development is to monitor child development at the Puskesmas/Posyandu or by paying attention to the children's language development table according to their age.